Compassion as a tool for allyship and anti-racism - Karnaze, Melissa M.; Rajagopalan, Ramya M.; Eyler, Lisa T.; Bloss, Cinnamon S. (Frontiers in Psychology, 2023)
Racist systems, policies, and institutions subvert the quality of life for minoritized individuals and groups, across all indicators, from education and employment, to health, to community safety. Reforms to address systemic racism may be accelerated with greater support from allies who identify with the dominant groups that derive advantage from such systems. Although enhancing empathy and compassion for impacted individuals and groups may foster greater allyship with and support of minoritized communities, little work to date has assessed the relationships among compassion, empathy, and allyship. After reviewing current work in the area, this perspective offers insights into the utility and specific components of a compassion-based framework that can be used to combat racism, using findings from a survey study in which we investigated the relationship between validated psychometric measures of compassion and allyship with minoritized communities. Several sub-domains of compassion, as measured among individuals identifying as non-Black , correlate significantly with levels of felt allyship with Black or African American communities. These findings inform recommendations for compassion-focused research, including development and testing of interventions to promote allyship, advocacy, and solidarity with minoritized groups, and support efforts to undo longstanding structural racisms that have patterned inequality in the U.S.